PENGARUH RISIKO PERUSAHAAN, UKURAN KAP, DAN KOMPLEKSITAS PERUSAHAAN TERHADAP FEE AUDIT - Maryani, Dini; Khuluqi, Khusnul (LPPM Universitas Bina Bangsa, 2025)
This research aims to explain and provide empirical evidence regarding the influence of Company Risk, KAP Size and Company Complexity on Audit Fees. This research was conducted by analyzing the financial reports of companies in the Consumer Non-Cyclicals sector listed on the Indonesian Stock Exchange (BEI) during the period 2018 to 2023. The sample used in this research was 30 Consumer Non-Cyclicals companies for the period 2018 to 2023. In 2023 using a purposive sampling technique. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. Based on the results of this research, it shows that (1) Company Risk, Size KAP and Company Complexity simultaneously have a significant effect on Audit Fees, (2) Company Risk has no significant effect on Audit Fees, (3) KAP size has a significant effect on Audit Fees, However (4) Company Complexity has no significant effect on Audit Fees.